Teleworking in the public sector: a case study of Selangor / Nurulhuda Ma'arof, Kamalia Azma Kamaruddin and Nor Shahida Mohamad Yusop - Ma'arof, Nurulhuda; Kamaruddin, Kamalia Azma; Mohamad Yusop, Nor Shahida (Universiti Teknologi MARA, 2023)
Telework, an arrangement of jobs using ICT with flexible job locations, has been associated with its conflicts as an employment approach that leads to the refusal of its implementation especially in the public sector. Despite increasing efficiency in individual and organizational aspects, there is still uncertainty in the public organization to accept teleworking. Hence, understanding of factors influencing perception and attitude towards teleworking among public officials that could lead or hinder the acceptance of telework approach is critical for a successful teleworking adoption by the public organization in the future. In the absence of study on telework in the public sector, this study clarifies the intention of public officials particularly in Selangor to behave whether in favour of or against an introduction of teleworking approach by assessing the factors associated with their intention to telework. Using the existing research model namely Decomposed Theory of Planned Behaviour (DTPB), its main elements which consist of attitude, subjective norms and perceived behavioral control were quantitatively validated through online questionnaires. This study revealed that all three (3) factors in DTPB had a positive significant association on Selangor public officials' intention to telework. Other than setting the basis for public service preparedness and adaptation towards new employment approaches, this study contributes to policy and research practice by providing new insights into the public officials' adoption of telework in the public sector.